2012
DOI: 10.1016/j.yebeh.2012.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Cooing- and babbling-related gamma-oscillations during infancy: Intracranial recording

Abstract: We determined the spatio-temporal dynamics of intracranially-recorded gamma-oscillations modulated by spontaneous cooing and babbling, which are considered to embody pre-linguistic language behaviors during infancy. Electrocorticographic (ECoG) signals were recorded from 110 cortical sites in the right hemisphere of a 10-month-old girl with focal epilepsy. ECoG signals were time-locked to the onset of cooing or babbling. The amplitudes of gamma-oscillations during vocalizations were compared to those during pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…Brain activity during spontaneous, non-experimental communication, however, is a largely unexplored phenomenon, which has been referred to as 'the dark matter' of cognitive neuroscience [40]. To bridge this gap, several labs worldwide have started investigating the neuronal activity underlying language in extraoperatively recorded ECoG in increasingly naturalistic experiments [3,4,[41][42][43][44] as well as in conditions of non-experimental, real-world communication [18,20,21,23,[45][46][47][48][49]. Their reported effects align with previous experimental findings (cf.…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…Brain activity during spontaneous, non-experimental communication, however, is a largely unexplored phenomenon, which has been referred to as 'the dark matter' of cognitive neuroscience [40]. To bridge this gap, several labs worldwide have started investigating the neuronal activity underlying language in extraoperatively recorded ECoG in increasingly naturalistic experiments [3,4,[41][42][43][44] as well as in conditions of non-experimental, real-world communication [18,20,21,23,[45][46][47][48][49]. Their reported effects align with previous experimental findings (cf.…”
Section: Introductionmentioning
confidence: 54%
“…With only about a dozen recent exceptions [18,20,21,23,[45][46][47][48][49], neurolinguistic and direct speech BCI studies to date are based on experiments. Investigation of non-experimental, real-word language is a novel, largely unexplored approach.…”
Section: Developments In Ecog Research On Speech Production Using Incmentioning
confidence: 99%
“…It still remains unknown at what point each brain region begins to show language-related gamma-augmentation maximally involving 80–100 Hz. Our recent ECoG study of a 10-month-old patient with right-sided seizure focus reported that spontaneous cooing and babbling elicited gamma-augmentation ranging up to 100 Hz in the right inferior-Rolandic and superior-temporal regions (Cho-Hisamoto et al, 2012). Since few infants have the capability to complete a naming task, studies including infants using passive auditory or somatosensory tasks may be warranted to determine the developmental changes of event-related gamma-augmentation.…”
Section: Discussionmentioning
confidence: 99%
“…They will show excitement by waving their arms and legs, much to the delight of their caregivers. Between 6 and 12 months of age, the coos turn into playful babbles that may start to sound like words as they near the 1-year mark [9]. They will shout loudly to get attention, show affection, and start to understand cause and effect (e.g., if I cry, then something will happen).…”
Section: Typicalmentioning
confidence: 99%